2021
DOI: 10.7717/peerj.12303
|View full text |Cite
|
Sign up to set email alerts
|

Punicalagin, a pomegranate compound, induces apoptosis and autophagy in acute leukemia

Abstract: Background Punicalagin is the major phenolic compound found in pomegranate peels. It has several reported medical benefits, including antioxidant, anti-inflammatory, and anticancer properties. The present study investigated the anti-leukemic effects and the molecular mechanism of punicalagin on NB4 and MOLT-4 leukemic cell lines. Methods Leukemic cells were treated with punicalagin and cell viability was determined using MTS assay. Apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Apoptosis and autophagy can be synergistic or opposite processes because a complex interplay between them exists at different signaling levels. For example, punicalagin exerts the cytotoxic effect by suppressing proliferation and promoting apoptosis and autophagy by activating the caspase cascade, altering Bax and Bcl-2, and regulating autophagy via mTOR/ULK1 signaling in human NB4 and MOLT-4 leukemia cell lines [68]. Punicalagin induces apoptotic and autophagic cell death in human U87MG glioma cells [69].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis and autophagy can be synergistic or opposite processes because a complex interplay between them exists at different signaling levels. For example, punicalagin exerts the cytotoxic effect by suppressing proliferation and promoting apoptosis and autophagy by activating the caspase cascade, altering Bax and Bcl-2, and regulating autophagy via mTOR/ULK1 signaling in human NB4 and MOLT-4 leukemia cell lines [68]. Punicalagin induces apoptotic and autophagic cell death in human U87MG glioma cells [69].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, P. granatum' cytotoxic effects are brought on their physiochemical interaction with intracellular genetic materials (Khan et al, 2021). Previous studies suggests that P. granatum' cytotoxic effect may possibly be brought about by the stimulation of apoptosis (Cheshomi et al, 2022;Mollaei et al, 2022;Subkorn et al, 2021;Teniente et al, 2023;Turrini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, continuous prolonged exposure to H. pylori decreases autophagy by inhibiting maturation of the autophagosome. Additionally, Subkorn et al [ 14 ] indicated that punicalagin (a pomegranate compound) can induce autophagy in acute leukemia. Moreover, another study by Zhang et al [ 15 ] showed that, urolithin A (a pomegranate metabolite) activates autophagy in pancreatic β-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate fruit ( Punica granatum L., family Lythraceae) is rich in polyphenolic compounds and anthocyanins and has antioxidant, anticancer, anti-inflammatory, and antiulcer activities [ 10 , 11 , 12 , 13 ]. Intriguingly, punicalagin (a pomegranate constituent) and urolithin (a pomegranate metabolite), can induce autophagy in acute leukemia [ 14 ] and pancreatic β cells [ 15 ]. Pomegranate total peel extract demonstrated anti- helicobacter effect in vitro and in vivo [ 16 ].…”
Section: Introductionmentioning
confidence: 99%